School Library: Between Hope and Reality - Firmansyah, Firmansyah (PPSDP International Journal of Education, 2022)
Libraries, with recent innovations, should be seen not just as organizations that manage books and other publications, but also as institutions that manage information resources using information technology. The School Literacy Movement should be able to reestablish the school library's primary function as the hub of student literacy information. Not only can renewable management improve school literacy, but it can also improve the operation of the library. Educational libraries should be used to address substantive issues and incorporate them into school goals.